AN ANALYSIS OF THE LEVEL OF LEARNING BURNOUT AT SMAN 1 MANGGIS - Intari, Ni Komang Putri; Dambayana, Putu Eka; Paramartha, A.A. Gede Yudha (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2025)
This research was conducted at SMA N 1 Manggis academic year 2022-2023. The purpose of this research is to analyze the level of learning burnout among SMA Negeri 1 Manggis students. Learning burnout is a condition in which students are emotionally detached, unmotivated, and have a negative attitude toward the learning process. This study used a quantitative descriptive method with data collected through questionnaires completed by 244 students from twelfth grade. The questionnaire consists of 30 questions valid with a reliability score of 0.919. The variables examined included emotional dimension, physical dimension, cognitive dimension, and loss of motivation. The research found that students in grades XII have a medium-level category of learning burnout, with a mean score of 80.91. Each indicator in the dimension specifies a different level category. The level showed the respondent experienced learning burnout in all aspects. Factors such as academic performance, learning methods, body condition, family support, and poor social environment are identified as primary causes of learning burnout. This research provides recommendations for school to improve their programs.